Clinical significance of GCF sIL-6R and calprotectin to evaluate the periodontal inflammation. (November 2017) - Kajiura, Yukari; Lew, Jung-Hwan; Ikuta, Takahisa; Nishikawa, Yasufumi; Kido, Jun-ichi; Nagata, Toshihiko; Naruishi, Koji
Background: Periodontitis is an inflammatory disease. The aim of this study was to investigate whether the soluble form of interleukin-6 receptor (sIL-6R) and calprotectin concentrations in gingival crevicular fluid are useful biomarkers in the evaluation of periodontitis. Methods: First, a cross-sectional study was performed. A total of 34 periodontitis patients were enrolled and the gingival crevicular fluid samples were collected from the healthy and inflamed sites of periodontal pockets in each patient. The relationship between periodontal condition and gingival crevicular fluid sIL-6R and calprotectin concentrations was analysed statistically. The cut-off values of gingival crevicular fluid sIL-6R and calprotectin concentrations for the evaluation of periodontitis were determined using a receiver operating characteristic curve. Next, by using enzyme-linked immunosorbent assay, it was examined whether calprotectin induces sIL-6R production in THP-1 macrophages. Results: Both gingival crevicular fluid sIL-6R and calprotectin concentrations were significantly higher in the inflamed sites than in the healthy sites ( P  < 0.0001). The cut-off values of gingival crevicular fluid sIL-6R and calprotectin concentrations for the evaluation of periodontal inflammation were as follows: sIL-6R: 43.5 pg/site; calprotectin: 134.3 ng/site. In the in vitro study, calprotectin significantly induced sIL-6R production in THP-1 macrophages ( P  < 0.01). Conclusions: Both gingival crevicular fluid sIL-6R and calprotectin concentrations are significant biomarkers in the evaluation of periodontal inflammation.